PP.10.06: EARLY VASCULAR AGEING IN NORMOTENSIVE SUBJECTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. COMPARISON WITH YOUNG HYPERTENSIVE PATIENTS. (June 2015) - Morreale, M.; Mulé, G.; Ferrante, A.; D'Ignoto, F.; Geraci, G.; Cottone, S.
Abstract : Objective: Aortic pulse wave velocity (aPWV), is one of the most important markers of vascular aging. It is well known that connective tissue diseases are associated with accelerated atherosclerosis, but only a few data are available about aPWV in patients with systemic lupus erythematosus (SLE). The aim of this study was to evaluate early vascular aging, assessed by measuring aPWV, in a group of normotensive patients with SLE and to compare these subjects with a group of young essential hypertensive (EH) individuals Design and method: Cross-sectional study.We have enrolled 39 normotensive SLE subjects (mean age: 38.7 ± 8.3 years) matched for age with a group of essential hypertensive patients (mean age 38.7 ± 9.8 years). Each patient has been underwent aPWV measurement through an oscillometric device (Arteriograph). Results: As for selection, systolic and diastolic blood pressure values were significantly lower (121/71 ± 14/9 mmHg) in the SLE patients when compared to those of the hypertensive subjects (151/98 ± 14/8 mmHg; p < 0.001). Despite this difference regarding BP, aPWV was similar in the two groups, being 9.1 ± 2, 9m/sec in SLE subjects and 9.05 ± 2 m/sec in the group of young essential hypertensive patients (p = ns). In both groups aPWV was greater than that of the normal population in the same age category (6.5 m/s). Conclusions: Our results seem to suggest that SLE has the same deleterious impact on vascular aging as well as high blood pressure. It is very likely that this unfavourable effect of SLE is mediated by chronic inflammation.